Data Mining through Internet search engines: the case for Islamic management materials - Mhd Sarif, Suhaimi; Ismail, Yusof (2010)
The study is carried out to ascertain relative availability of the materials of Islamic management using data mining through the Internet search engines (ISE’s). The contents of thirteen ISE’s are analysed using a specially created format. The present study established the relative ratios of the coverage of selected terms in terms of number of hits shown within each ISE. The ratios are obtained by dividing the hits for a search term into the means (average) of comparable hits as the standardized denominator. The results of the analysis show that the ISE’s contain scarce amount of materials on Islamic management.